PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH DENGAN STRATEGI PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN HASIL BELAJAR MATERI BANGUN RUANG SISI DATAR KELAS VIII MTs.N 4 KOTA PALU : The Application of The Problem-Based Learning Model With Diferentiation Learning Strategies to Improve Learning Outcomes on Topics of Polyhedra for Class VIII MTs.N 4 Palu City - Dwiyanti, Risna; Rizal, Muh.; Sukayasa, Sukayasa; Nurhayadi, Nurhayadi (Aksioma, 2025)
This study aims to obtain a description of the application of problem-based learning model with differentiation learning strategies to improve learning outcomes on topics of polyhedra for class VIII B MTs.N 4 Palu City. The subjects in this study were 32 students of class VIII B MTs.N 4 Palu and 3 students were selected as informants. This study is a Classroom Action Research (CAR) that refers to the Kemmis and Mc. Taggart research design. This study was conducted in two cycles that followed the phases of the Problem-Based Learning model, namely (1) Student orientation to the problem, (2) Organizing students to learn, (3) Assisting individual and group investigations, (4) Developing and presenting work results, (5) Analyzing and evaluating the problem-solving process. By combining differentiated learning strategies in the phase of organizing students to learn and the phase of guiding individual and group investigations. In cycle I, the number of students who completed was 11 students with a completion percentage of 39.3% and in cycle II, the number of students who completed was 21 students with a completion percentage of 75%. Based on the results of the study, it can be concluded that the application of the Problem-Based Learning model with a differentiation learning strategy can improve the learning outcomes on topics of polyhedra for class VIII MTs.N 4 Palu city.